Exploring social interaction and its attributes among students via mobile social forum / Nur Atikah Kamaruddin - Kamaruddin, Nur Atikah (2015)
The landscape of social interaction between students in a university environment is changing through the introduction of online social network. However, there is not much research about how the student uses online social forum which dedicated for student only and at the same time fostering sense of community among the student. The small volume of research also caused from a less number of dedicated online forums that fostering the student in university environment especially in Malaysia. There are journals suggesting most social interaction is between student and lecturer. This is due to less possible way to verify the interaction between students with students. Therefore, this research aims at identifying the elements of social interaction that could foster student interaction by designing and developing online social forum, StudSquare.com. This online forum is only dedicated to FSKM UiTM Shah Alam students. Through the observation and content usage on Studsquare.com and individual survey, adoption from Rovai Classroom Community four dimension and Rovai Classroom Community Scales, the result shows significant value of total of 60 students and alumni on connectedness and belongings dimension towards other student, other than learning dimension. This result will give significant value for student in tightening the community bonding and help the body of knowledge in getting a better view of student social interaction expending the community bounding to the outside of faculty environment.